Living with female rats exposed to restraint stress during pregnancy caused depressive‐like behavior in male rats and stress‐induced apoptosis. Issue 7 (16th July 2021) - Kocahan, Sayad; Akillioglu, Kubra; Sencar, Leman; Sahin, Leyla; Cevik, Ozge Selin; Taskin, Eylem; Guven, Celal; Boga, Ayper; Polat, Sait
Abstract: Objective: Maternal mood disorders such as postpartum depression (PPD) can negatively affect the lives not only of mothers but also of partners. The purpose of this study investigates emotional behavior and hippocampal apoptosis alterations of the male live with a postpartum depressed female. Methods: Pregnant rats in the stress group were exposed to restraint stress (RS). The male rats who shared the same cages were not exposed to RS. To explain the consequences of depressive‐like behavior and anxiety, animals were exposed to the forced swim test (FST), open‐field test (OFT), and elevated plus maze (EPM). The apoptotic cell number was detected by terminal deoxynucleotidyl transferase (Tdt)‐mediated dUTP biotin nick‐end labeling (TUNEL) staining. Results: According to FST, PPD caused more immobility, reduced swimming, and climbing compared to control groups in the stressed female and male ( p  < 0.05). For the crossing number of squares in the center area, the main effect of the group was significant ( p  < 0.05). Stressed groups have a higher crossing number of squares in the center area compared to control groups. In the OFT, there was a significant increase in the time spent in the center area in the stress female and male group compared to the control female and male group ( p  < 0.05). For the EPM, time spent in the close arms was increased in the control male and stress male compared to the stress female group ( p  < 0.05). Female and male rats with PPD demonstrated apoptosis in neuron and glial cells in the hippocampus. Conclusions: The present study demonstrates that RS results in PPD in females. Furthermore, it implicates RS as a potential risk factor for the development of postpartum mood disorder in males. Most of the studies on paternal PPD have been done by using self‐report questionnaires. Studies on physiological and hormonal changes during the postpartum period among fathers would provide information on biological factors of depression. Abstract : (a) Pregnant rats in the stress group were exposed to restraint stress three times daily to 45 min in transparent plastic cylinders under bright light. (b) The male rats and offspring have shared the same cage with female (stressed) rats, without any additional stress exposure through the pregnancy and postnatal 3 days. (c) For evaluating the anxiety and depression‐like behavior, open‐field test (OFT), elevated plus maze (EPM), and forced swim test (FST) tests were executed. (d) The hippocampus was dissected from the rats' brains. (e) The apoptotic cells were detected in the hippocampus slices by terminal deoxynucleotidyl transferase (Tdt)‐mediated dUTP biotin nick‐end labeling (TUNEL) staining. The present study indicated that restraint results in postpartum depression in females, and it is a potential risk factor for the development of postpartum mood disorder in males. This study showed that postpartum depression not only altered the female's mood, behavior, and brain morphology but also affected male rats.